Indigenous peoples, cultural diversity and the right to self-determination: from the international law to the Latin American constitutionalism - Souza Alves, Rodrigo Vitorino (Pontificia Universidad Católica del Perú, 2015)
Indigenous peoples have valuable ancestral cultures and makeimportant contributions to society in general. However, despite the recognized value of these peoples and their cultures, their most basic rights have been violated for a long time. The postcolonial era did not end the internal«colonization», because in many places the locals are still treated as inferior to the other inhabitants within the territory of the Country. Nevertheless, the international law is moving in the opposite direction, recognizing the dignityand the rights not only of individuals but also of indigenous peoples, ensuring cultural security. In recent decades, relevant international  instruments have been adopted, inspiring the constitutional reforms and human rights initiatives for the protection of indigenous peoples. This article aims to investigate how the legal recognition of self-determination of the indigenous peoples contributes to the protection and promotion of their culture. On that matter, the first section of the paper concentrates on the conceptual discussion on indigenous peoples, as well as the legal-political relationship models between them and the State. Second, the rights of the indigenous peoples will be examined from the perspective on international law, with special emphasis on the collective self-determination right. In the last section, the Latin American Constitutions will be studied, in order to present the situation of the indigenous self-determination in Latin American.